Policy on handling street children in Indonesia: conformity with the princi-ples of the state of law and good governance - Diah Turis Kaemirawati; Susetya Herawati; Eka Ari Endrawati; Ratna Dewi; Endang Sri Sulasih (LEGAL BRIEF, 2025)
The policy in handling street children is a required aspect of the state's duty to guarantee rights for children, as mandated by the rule of law and good governance standards. The researcher has as it's target measured the difference between ideal principles under the rule of law metrics such as certainty constructions, fairness equations, equitable distribution of social costs (which benefits more people than capitalism gives in general) and protection for children who are not old enough to protect themselves and the specific policies that emerge in Indonesia's traditional manner of dealing with street kids. This study also examines how public policy governance can be strengthened to be more aligned with the principles of accountability, transparency, effectiveness, institutional coordination, and responsiveness. Based on a study of various bureaucratic policies and practices at the central and regional levels, it was found that there was a discrepancy between the values ??that should be the basis for policy formulation and the conditions of practice in the field. The gap can be seen in the weak database, limited basic service facilities, lack of coordination across institutions, and policy orientation that tends to be reactive and unsustainable. This study recommends strengthening public policy governance through institutional integration, more consistent planning, more accurate data utilization, and the application of an approach centered on the fulfillment of children's rights to ensure policy conformity with the principles of the rule of law and good governance.